B-mode ultrasonography of herniated cervical discs in young people - Abdullaiev, Ruslan; Voronzhev, Igor (ScienceRise: Medical Science, 2022)
The aim: to evaluate the possibilities of ultrasonography in the diagnosis of herniated cervical intervertebral discs in young people. Material and methods: an analysis of the results of USG in 29 patients with cervical IVD hernia revealed by MRI from 123 patients aged 18–44 years, with complaints of neck pain of varying intensity, duration, and irradiation. 23 (79.3 %) patients had clinical signs of cervical radiculopathy. The results of the ultrasonography (USG) were compared with MRI. USG was conducted on a Philips HD 11XE scanner using a 4–9 MHz frequency transducer; MRI – General Electric, Signa HDI, 1.5T. Results: in 13 (44.8±9.2 %) cases the hernia was registered in the C5-C6 disk, in 12 (41.4±9.0 %) – in the C4-C5 disk, in 2 (6.9±4.7 %) – in the disk C3-C4 and in 2 (6.9±4.7 %) – in the disk C6-C7. In discs C5-C6 and C4-C5 hernia was formed significantly (p<0.01 and p<0.001) more often than in discs C2-C3 and C6-C7. Paramedian hernia was diagnosed in 13 (44.8±9.2 %) cases, posterior – in 12 (41.4±9.1 %), median – in 4 (13.8±6.4 %). Paramedian and posterolateral hernias were registered significantly more often than median (p<0.01 and p<0.05). Conclusions: A direct sign of a herniated cervical intervertebral disc is its uneven protrusion with a discontinuous image of the fibrous ring into the lumen of the spinal canal and spinal nerve canal more than 4 mm. An indirect sign of a herniated cervical intervertebral disc is a local deformation of the anterior epidural space with the absence of its visualization. Ultrasonography is a reliable method for diagnosing herniated cervical intervertebral discs, both in segments and inside the spinal canal. The method can be used to find out the causes of neck pain in young people